COLONIAL STRATEGIES OF TRADE CONTROL AND RESTRUCTURING OF MERCANTILE REALM IN EARLY MODERN MALABAR - K M, Dileepan (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The arrival of European colonial powers in Malabar marked a transformative shift in the region's trade dynamics. It significantly altered the region's mercantile realm, transforming it from a diverse, locally managed trading network into a colonial-controlled economic system with monopolistic practices and maritime control at the forefront of colonial strategies. This study explores the role of the Portuguese, the Dutch, and the British in monopolizing Malabar's lucrative spice trade, particularly pepper, through a combination appropriation and negotiation strategies. It investigates the colonial approach to controlling maritime routes, establishing fortified ports, and creating exclusive trading rights, which not only disrupted local economies but also reshaped global trade networks. By examining key events such as the Portuguese imposition of the cartaz system, the Dutch establishment of trade monopolies, and the British efforts to secure critical trade routes, this study highlights how colonial powers restructured the region's economic landscape. It also highlights how local people, including regional rulers and indigenous merchants, negotiated with these colonial interventions to maintain their economic interests and autonomy. This analysis contributes to a deeper understanding of the interplay between colonialism, commerce, and indigenous responses, and how these interactions influenced the broader course of global trade during the early modern period.